Language Variations in Arabic Food Vlogger on the S7S YouTube Channel: A Sociolinguistic Study - Sani, Azmi; Astari, Rika; Seman, Mohammad (Syarif Hidayatullah State Islamic University of Jakarta, Indonesia, 2024)
Language variation is a person's dissimilarity in expressing an expression. The existence of language variations means that someone with other individuals has differences in language. The inequality makes humans more diverse. Food vlogger-type content was taken by researchers. The Food vlogger's content was rich in words or sentences, and they used sentences that were easy to understand because their content provided various information related to food. This research aimed to describe the language variations of the Arabic YouTuber Hussain Sallam on the S7S YouTube channel. The research method that has been used qualitative descriptive method. The results above showed four language variations: code-switching, code-mixing, jargon, and slang. From this, we could conclude that all the detected language variations were included in informal language.